Correla????o entre pena pecuni??ria e valora????o econ??mica dos recursos naturais degradados na perspectiva da an??lise econ??mica do Direito - Machado, C??ssio (2016)
The aim of this study is to verify the correlation between the economic monetary penalty attributed to environmental crimes agents and their damage, based on the economic analysis of law. The study takes an interdisciplinary approach, in that it seeks to demonstrate the close relationship between law and economics to identify the economic and social impacts of environmental crimes and for their valuation degraded property. To support the work, the environment was characterized as well legal, listing up the penalties charged to agents of crimes against him; described is the social function of the sentence and its value to the law; They were listed basic principles of Traditional Theory of Criminal Law and Economic Theory of Crimes and Punishments and analyzed briefly fines charged against environmental crimes agents, with regard to the said correlation. The research was guided by questions such as: how are valued monetized degraded natural resources for penalty purposes for environmental crimes? Environmental crimes, the penalty has maintained its sense of "sensitive and powerful means to quell the despotic spirit that returned to plunge society into chaos"? "As the rules (or feathers) can affect behavior and how they can be modified to generate more beneficial behavior for society?" The conclusion was that there is a positive correlation between the monetary penalty attributed to environmental crimes agents and their damage done.